Desenvolvimento de um sistema para monitoramento acústico da Análise de Composição Química em Campo - Souza, Frederico Costa (2018)
The objective of this work was the design, manufacture and validation of an acoustic monitoring system of the chemical analysis process, in order to alert the operator of the Belec Compact Port HLC® portable equipment used in the analysis of chemical composition in the field about the validity of the results. In order to investigate the effect of vertical distance and surface geometry factors in the results of the analysis of the chemical composition of API X65 steel a complete factorial design 3x8 was proposed. The Analysis of Variance (ANOVA) was applied, and it was concluded with a 95.45 % confidence level that the investigated factors (vertical distance and geometry of the evaluated surface) and the interaction between them produced statistically significant effects in the values of the response variable (% of weight) of the steel X65. A low cost acoustic measurement system was designed, built and validated to monitor the frequencies of the noise signals emitted during the chemical composition analyzes in situ. A program in LabVIEW® has been developed and validated for acquisition of acoustic signals. The developed embedded system was efficient in the monitoring of the noise signals, presenting nominal range of 11 Pa RMS and resolution of 0.04 Pa RMS. The sound pressure measurement uncertainty (U) obtained for the inputs of 1 Pa RMS and 10 Pa RMS was U = 0.02 Pa RMS for a coverage factor k = 1.96 and a coverage probability of 95.45%. The cost of the embedded system was R$ 430 (USD 115.59, based on the quotation on 06/14/2018). Finally, a reliable criteria for the chemical composition analysis acceptance was defined.